Enhancement Quality Learning Student in implementing Project Strengthening Profile Pancasila Students (5P) with Lifestyle Theme Continuing at Karya Pembangunan Baleendah High School (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
In the context of post-pandemic recovery of learning from Covid 19, the Ministry of Education and Culture 2022 will roll out the Independent Curriculum Implementation (IKM) program for the Independent pathway category which consists of 3 categories, namely Independent Learning IKM, Changing Independent IKM, and Independent Sharing IKM. Karya Pembangunan (KP) Baleendah High School is a school implementing the Independent Changing IKM category which must implement the Independent Curriculum in the 2022/2023 academic year for class X students, using teaching tools from the government or adapt them according to the conditions of Baleendah KP High School, as well as implementing the Cocurricular Strengthening Project Pancasila Student Profile (5P). In realizing the Pancasila student profile which acts as the main reference that directs educational policies including being a reference for educators in building the character and competence of students, the implementation is carried out through intracurricular, co-curricular activities (5P project), extracurriculars and school culture/climate. The form of community service carried out at KP Baleendah High School is a form of training in carrying out co-curricular activities of the Pancasila Student Profile Strengthening Project (5P) with the theme "Sustainable Lifestyle", through the topic "SMA KP BERHIAS" (SMA KP Clean, Green, Innovation, and Creation ) which is the second choice of theme, which previously implemented the Bhineka Tunggal Ika theme. The 3 dimensions of the Pancasila Student Profile selected are the most relevant dimensions and are a priority scale as the goal of the Sustainable Lifestyle Project, namely (1) Faith, Fear of God Almighty and noble character; (2) Mutual Cooperation; and (3) Creative. This research method uses a qualitative approach to the type of descriptive research. This research was conducted using observation guidelines, interviews, and documentation with research sources, namely the school principal, teachers who served as coordinators, project facilitator teams, and class X students. The results stated that in the activities of the Pancasila Student Profile Strengthening Project (5P), which was carried out, the ability of teachers as coordinators and facilitators of the 5P project has increased compared to the implementation of the previous 5P Project, so this has a positive impact on student development in implementing the Pancasila Student Profile Strengthening Project shown by the emergence of student characters, namely morals in nature who realize themselves as part of the environment, have a responsibility, compassion, and care for the natural environment, realizing that as a human being, he has a duty to protect and preserve nature as God's creation. This made him realize the importance of caring for the environment as an element of the dimension of Faith, Fear of God Almighty, and noble character. Demonstrate the ability to cooperate, care for others, and the ability to share which are elements of Mutual Cooperation, and show creative abilities that are able to modify and produce something meaningful, useful, and impactful. The inhibiting factors for the Strengthening Pancasila Student Profile (5P) Project include the limited learning environment for the project because the learning environment between SMA and SMK students is still unified, there are also teachers in a team of facilitators who always rely on other teachers so that when the teacher they rely on cannot attend which sometimes lacks the provision of infrastructure, and still 5P project activities do not go according to the flow of project activities that have been prepared due to the teacher's lack of understanding of the 5P concept